The Relationship of the 5th Batch Campus Teaching Program to Literacy and Numeracy Skills in Elementary Schools - Muhammad Misbahudholam AR; Asmoni Asmoni; Kurratul Aini; moh wardi (AL-ISHLAH: Jurnal Pendidikan, 2024)
The research was carried out to determine the influence of the Class V Teaching Campus program on Phase C literacy and numeracy skills in elementary schools throughout Sumenep Regency. The type of research used is causal-comparative research, or ex-post facto. The research was conducted in 13 elementary schools at Class V teaching campuses across the Sumenep district. The research instruments used were questionnaires and literacy and numeracy test questions. This research data analysis uses simple linear regression analysis. Based on the results of testing the first hypothesis using simple linear regression analysis, the results obtained on literacy were obtained at a significant level of α = 0.05, and a sig value of 0.02 α = 0.05 was obtained. The regression equation obtained is Y = 27.955 + 0.624X. Students' literacy skills were 5.4%, while other factors outside the implementation of the Class V Teaching Campus program influenced 94.6%. Nemuration skills at a significant level of α = 0.05 obtained a sig value of 0.03 α = 0.05. The regression equation obtained is Y = 30.055+ 0.575X. Students' numeracy skills were 4.7%. Other factors impacted 95.3% of the population outside the Class V Teaching Campus. This research showed that implementing the Class V Teaching Campus Program significantly influenced the numeracy skills of Phase C Elementary School students in the Sumenep district.